Modified triple pelvic osteotomy for adult symptomatic acetabular dysplasia: clinical and radiographic results at midterm follow-up - Jiajun Wu; Yang Yang; Xiuhui Wang; Xiaoxiao Zhou; Changqing Zhang (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Acetabular dysplasia is the most common cause of secondary arthritis of the hip joint. Achieving maximum restoration of the acetabular coverage and medialization of the femoral head remains difficult with the original Steel triple pelvic osteotomy for acetabular dysplasia in children and adults. This study intended to answer the following questions: (1) Are the midterm functional results of our modified procedure favorable, particularly in relation to Harris scores? and (2) On the basis of the Tönnis grade, does this procedure has a different effect on radiographic parameters and functional results at midterm follow-up? Methods This study included 26 consecutive adult patients with symptomatic acetabular dysplasia (28 hips) who underwent modified triple pelvic osteotomy through two incisions between July 2005 and June 2012. According to the preoperative Tönnis grade, the patients were divided into T0 (Tönnis grade 0), T1 (Tönnis grade 1), and T2 (Tönnis grade 2) groups. Wiberg center-edge (CE) angle, Sharp acetabular angle, lateralization, and Harris scores were analyzed to assess the radiographic and clinical outcomes. Results The mean CE angle (28.43° [± 3.58°], p < 0.05), Sharp acetabular angle (36.39° [± 3.26°], p < 0.05), lateralization (16.82 mm [± 3.10 mm], p < 0.05), and Harris scores (89.07 [± 4.97], p < 0.05) at the last follow-up significantly improved compared to those preoperatively. Multiple comparisons of radiographic outcomes among the three groups indicated no significant difference (p < 0.05). Harris scores in group T2 were significantly lower than those in groups T0 (p < 0.05) and T1 (p < 0.05). No major complication was observed. Conclusions Our modified triple pelvic osteotomy for adult symptomatic acetabular dysplasia with early-stage osteoarthritis could lead to excellent radiographic outcomes, good clinical results, and lower complication rates.